(untitled) (Al-Academy, 2020)
The theatre is one of the main pillars of the human aesthetic thinking as it contains logical explanations for the public human life aspects outside time and environment. When we find that the directive philosophical thinking moving away from the stylistic constants and the virtual laws in taboos that control the accomplishment in terms of the traditional shapes, the employment and the theatrical reception. Some directors moved in post-modernism concepts in a perceptive that liberates thought from its natural context in thinking into an innovative perceptive. The aesthetic images are the basic premise in the prohibition of the philosophical thinking interpretation in order to move the directive thinking and this movement depends on the variable in sign mobility of the overall form in the theatrical process. This includes the suggested space and the innovative scenography away from the legal view that the director gives to his stylistic features. The research, here, introduces a directive model that adopts the pure thinking to constitute the aesthetic image through the philosophical variable of the director’s innovative thinking which bridges the difference between the constant and the variable in accomplishing the aesthetic image and its ingredients. The research, in its theoretical framework, consists of three sections and the procedural chapter addresses a thorough analysis of a theatrical show for the suggested directive model from the Polish theatre, the actor (Tadeusz Kantor) and an analysis of one of his theatrical shows using the intentional method. The theatrical show (the dead class) (1975). The researcher then reached at results driven from the analysis and conclusions.